Célébrer la puissance du lieu. De Gaston Bachelard à Val Plumwood - Raïd, Layla (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Ecological thinking is rooted in particular ecosystems, and associated to particular places. But the academic style of writing has limited power to make these roots and places visible. In her ecological critique of modern reason, the Australian philosopher Val Plumwood explores different forms of writing to express how thought is ancho- red in places. More generally, she argues that environmental philosophy overhauls the modern division between poetry and philosophy. We propose a dialogue between Val Plumwood et Gaston Bachelard. Before the development of ecological thought, Ba- chelard was confronted with the same problem of how to articulate poetry and rational philosophical knowledge. Keywords : Ecology, place, Plumwood, Bachelard